Clinical Implications of Serum Retinol-Binding Protein 4 in Asthmatic Children - Park, Yeo Hoon (The Korean Academy of Medical Sciences, 2009)
Recently the prevalence of both asthma and obesity have increased substantially in many countries. The aim of this study was to evaluate the role of retinol-binding protein (RBP) 4 in childhood asthma and its association with atopy markers, pulmonary function, and bronchial hyperresponsiveness in relation to obesity. We studied 160 children between the ages 6 to 10 yr, including 122 asthmatics and 38 controls. The body mass index, pulmonary function tests, and methacholine challenge tests were measured on the same day. Total eosinophil count, serum total IgE, serum eosinophil cationic protein, and serum RBP4 were measured in all subjects. There was no difference in serum RBP4 levels between the asthmatics and the control group. In all subjects or subgroups, serum RBP4 was not associated with total eosinophil count, serum total IgE, serum eosinophil cationic protein, or PC(20). There was no relationship between serum RBP4 and pulmonary function in female asthmatics. Forced expiratory volume in 1 second/forced vital capacity (FVC) and forced expiratory flow between 25% and 75% of FVC contributed to serum RBP4 in male asthmatics. Our findings show an association between RBP4 and pulmonary function in prepubertal male asthmatics. This relationship may indirectly affect the high prevalence of childhood asthma in males.